Analyzing project management trends in Indonesia: 2018-2023 international literature review - Yopie, Santi; Febriana, Helen (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The purpose of this systematic literature review is to investigate the evolution of project management worldwide from 2018 to 2023, focusing on the integration of modern project management approaches and the challenges faced in the context of Industry 4.0. The review aims to bridge the gap between academic theory and industry practice in project management within the Indonesian landscape. Research methodology: A structured search was conducted through the Scopus platform, with inclusion and exclusion criteria applied to ensure relevance to the topic. The methodology involved evaluating articles for quality and relevance, extracting key information, and systematically organizing data for analysis. The review followed the PRISMA guidelines to ensure a rigorous and transparent approach. Results: The review revealed a growing need for adaptive project management practices in response to technological advancements and cultural nuances. Key findings include the importance of organizational culture, the role of authentic leadership, and the challenges of implementing sustainable community development. The study also highlighted the potential impact of Generation Z on the economic and political landscape. Limitations: The confinement of the literature search to articles from accredited international journals accessed through Google Scholar and categorized from Scopus 1 to Scopus 4, which may have excluded relevant studies. Additionally, the practical application of these insights in real-world settings was not extensively explored.   Contribution:  This review contributes to a deeper understanding of project management in Indonesia, offering insights into the challenges and opportunities within the field. It provides a foundation for future research and improved practices, emphasizing the need for project management professionals and scholars in Indonesia to explore innovative approaches and remain agile in the face of change.